Depelopment Of Pop-Up Book Media For Sexual Education - Asmidar Parapat; Sofni Indah Arifa Lubis; Zannatunnisya; Rahma Aulia (Yayasan Multidimensi Kreatif, 2024)
The Indonesian Child Protection Commission (KPAI) recorded more and more cases sexual violence that occurs in Indonesian children. In 2022 there are around 393 victims of sexual violence from 66 perpetrators. Meanwhile, at the beginning of 2023, namely from January to February, sexual violence cases have reached 117 victims with 22 perpetrators. Facts about the increase in sexual violence that occurs in children making us aware of the importance of protecting children from the threat of sexual violence. Wrong One Effort Can Be Done to Protect Children from Cases of Sexual Violence namely by providing information and understanding of sexual education so that Children can protect themselves from the threat of sexual violence. In this study The author conducted research on increasing sexual knowledge to children through Media Pop-Up Book. This research aims to determine the feasibility of pop-up book media to improve educational understanding sexual in children aged 5-6 years. Kind this research is research and development or Research and Development (R&D) using the Borg & Gall model. The results of this research indicate that there has been an increase in sexual education for children aged 5-6 years in PAUD Ummul Habibah, Kelambir V Village, Hamparan Perak District, Deli Serdang Regency.